Hydration in sport and exercise - Burke, L. M. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
Hypohydration, defined as a deficit in total body water that exceeds normal daily fluid fluctuations, is typically set as a fluid loss equivalent to >2% of body mass. The evaporation of sweat provides the principle means of heat dissipation during exercise in the heat; typical sweat rates of 300-2000 mL/h during sporting activities are generally not matched by fluid intake, leading to hypohydration. Although there are shortcomings in the literature related to hypohydration and sports performance, it is likely that some scenarios (hot conditions, larger fluid losses and prolonged aerobic exercise) are more at risk of incurring impaired performance. Guidelines for fluid intake during exercise and sporting activity are contentious since they need to span situations in which it is easy to overdrink compared with sweat losses and others in which significant levels of hypohydration occur. Nevertheless, athletes can be guided to develop fluid intake plans that are suited to their specific needs.